Special Education in Rural Education: teacher education in public universities in Rio Grande do Sul - Graciele Marjana Kraemer; Luciane Bresciani Lopes; Liliane Ferrari Giordani (Universidade Federal do Norte do Tocantins, 2020)
How has Special Education been presented to teachers attending teaching courses in Rural Education? In order to answer this question, it is necessary to study how Special Education knowledges have been produced in teacher education intended for Rural Education. From a research into specific documents, we have analyzed Pedagogical Projects of teaching courses in Rural Education, and Teaching Plans of disciplines addressing Special Education, in five public universities in the state of Rio Grande do Sul. We have found that Special Education knowledges have been marked with invisibility, isolation and fragmentation in relation to other curricular knowledges in Rural Education. Hence, we should highlight the need to understand teacher education as a practice requiring continuing investments in the constitution of a co-responsibility culture. This culture may be produced through a dialogue between different fields of knowledge, interconnection of methodological strategies, investments in education, and detachment from the paradigm of inclusion of knowledges that are exclusive to the field of Special Education.